Bimbingan Belajar Di Curug Tangerang - Wiyun Tangkin; Wiputra Cendana (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
A weak level of economic capacity (marginalized people) does not only provide less opportunities for obtaining a qualified education at school but also opportunities outside of school. Parents are unable to provide additional course or tutoring class for their children which makes their children’s understanding towards the learning material at school even worse as a result, children do not like school, so it can be predicted that learning outcomes will not be optimal. Based on these needs, UPH-Teachers College held tutoring at Perum Griya Karawaci, Curug-Tangerang. This tutoring aims to provide provision in the form of additional learning and assistance for children to learn from kindergarten, elementary, junior high and high school levels. The material taught is adjusted to the school material of each student. The play-learning method will be applied to kindergarten-Grade 3 elementary school students while for grade 4 elementary school students onwards it will be adjusted to the material being taught. This tutoring activity is held in 2 meetings per week, and those who are teaching are students of the Faculty of Education - Teachers College who have been previously selected. The evaluation of this activity after running from the beginning to the middle of 2019 resulted that this activity helps students improve reading, writing and arithmetic skills for kindergarten-elementary school students and improves Mathematics skills for junior high school students.